EFFECT OF SITAGLIPTIN AND VILDAGLIPTIN ON WOUND HEALING IN MALE WISTAR RATS - AN EXPERIMENTAL STUDY - Angadi, Netravathi B; Kagal, Urmila; Timshetti, Somaling (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Diabetes mellitus (DM) is a spectrum of common metabolic disorders, arising from a variety of pathogenic mechanisms. With an increasing incidence worldwide, DM will be likely a leading cause of morbidity and mortality in the future. Delayed wound healing in diabetes is a major source of morbidity and mortality. Sitagliptin and Vildagliptin are novel antihyperglycemic agents used for the treatment of DM. The present study was planned to investigate the effect of Sitagliptin and Vildagliptin on various wound healing models in male Wistar rats. Methods: Male Wistar rats (150â€“200 g) were divided into three groups, i.e., control, Sitagliptin, and Vildagliptin (n=6 animals in each group) for each wound model. Excision wound, resutured incision wound, and dead space wounds were inflicted under thiopentone anesthesia in male Wistar rats. The rats received Sitagliptin and Vildagliptin orally during the study period. Resutured incision was assessed by wound breaking strength; dead space wound was assessed by granuloma dry weight and histopathology of granulation tissue. In excision wounds, treatment was monitored by planimetry. Data were expressed as meanÂ±standard error of mean and analyzed by analysis of variance followed by Dunnett’s post hoc test. p<0.05 was considered statistically significant. Results: Sitagliptin and Vildagliptin significantly promoted the healing process in all three wound models studied. Histopathological studies revealed increased collagen content and granulation tissue in Sitagliptin and Vildagliptin groups. Conclusion: In all the three wound models studied, Sitagliptin and Vildagliptin promoted wound healing. The pro-healing effect of Sitagliptin and Vildagliptin needs to be explored clinically.